2022
DOI: 10.1016/j.ophtha.2021.10.010
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Remote Retinal Imaging Utilization and Payments in the United States

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 4 publications
2
7
0
Order By: Relevance
“…The primary outcome measure was time to eye exam within 1 year as indicated by remote retinal imaging or an in-person visit to an eye care provider. A claim was classified as remote screening if it included Current Procedural Terminology (CPT) codes for remote retinal imaging (92227 or 92228) by any provider, or for fundus photography (92250) billed by a non-eyecare provider, as previously described [ 15 ]. Otherwise, a claim was considered an in-person eyecare visit if the physician specialty was “ophthalmologist” or “optometrist,” and did not fall under the definition of remote screening.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The primary outcome measure was time to eye exam within 1 year as indicated by remote retinal imaging or an in-person visit to an eye care provider. A claim was classified as remote screening if it included Current Procedural Terminology (CPT) codes for remote retinal imaging (92227 or 92228) by any provider, or for fundus photography (92250) billed by a non-eyecare provider, as previously described [ 15 ]. Otherwise, a claim was considered an in-person eyecare visit if the physician specialty was “ophthalmologist” or “optometrist,” and did not fall under the definition of remote screening.…”
Section: Methodsmentioning
confidence: 99%
“…At a large integrated health system in Northern California, Ellis et al found that 55% of charges for remote DR screening using telehealth codes were denied by non-capitated insurance plans, and 40% were denied by private insurers [ 14 ]. Despite the rapid increase in teleophthalmology utilization across the U.S., insurance coverage has declined according to national insurance claims data, with disproportionate impact on vulnerable populations such as older, Black, and lower-income patients [ 15 ]. Building evidence to support the clinical benefit of remote DR screening may help encourage insurance payers to expand coverage for teleophthalmology services.…”
Section: Introductionmentioning
confidence: 99%
“…102 The proportion of claims paid for by Medicare Advantage was substantially lower than those paid for by other commercial payers. 102 Clinicians and health care administrators have cited low reimbursement as a barrier to the sustainability of teleophthalmology programs. 32 Patients also reported high out-of-pocket costs as a barrier to the use of teleophthalmology.…”
Section: Artificial Intelligence-based Image Analysismentioning
confidence: 99%
“…A US study using a national claims database found a 34.6% decline in the proportion of claims paid for remote retinal imaging from 2011 to 2020 102 . The proportion of claims paid for by Medicare Advantage was substantially lower than those paid for by other commercial payers 102 .…”
Section: Other Implementation Challenges and Opportunitiesmentioning
confidence: 99%
See 1 more Smart Citation